Analisis Wacana Kritis Model Norman Fairclough dalam Berita “Ketua Harian PSI Ahmad Ali Minta Kader Jaga Image Jokowi dan Kaesang” Pada Kompas.Com - Lukman Alfaris; Hari Bakti Mardikantoro; Rustono Rustono (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This study aims to uncover how language is used as an ideological instrument and a means of reproducing power in political reporting in the mass media. The focus of the study is directed at a critical discourse analysis of the news "PSI Daily Chairman Ahmad Ali Asks Cadres to Maintain the Image of Jokowi and Kaesang" published by Kompas.com, with the main question: how linguistic construction, news production and consumption practices, and socio-cultural contexts shape the meaning and ideology in the text. The method used is a qualitative approach through Norman Fairclough's three-dimensional framework—text analysis, discourse practices, and socio-cultural practices. The results of the study show that language in the text is used strategically to build a positive image of political figures and instill loyalty among party cadres. The study concludes that language functions not only as a means of communication, but also as a mechanism for reproducing power and political ideology in the public sphere.